(The Effect of Salt Concentration and Fermentation Time in "Ikan Peda") - Subardjo SK (Warta Industri Hasil Pertanian, 1990)
A study on the effect of salt concentration and the length of fermentation on "ikan peda" (a kind of fermented fish product) has been conducted. The fermentation was done in two steps; the first one using the variation of salt concentration (20, 30, and 40%), while the second was varied on its length of fermentation (10, 20, and 30 days). The first fermentation could be done for one week. The different length of second fermentation did not affect the product significantly. The result showed that the salt concentration of 30% gave the best quality of product with 47,75% moisture content and 1438% salt content.